Pengukuran Status Gizi Anak Usia Sekolah menggunakan Indeks Massa Tubuh di Kabupaten Takalar - Hamka Hamka; Sumarmi Sumarmi; Patmawati Patmawati; Dewiyanti Dewiyanti; Dina Oktaviana; Suardi Suardi; Ernawati Ernawati; Anita Kartini (Jurnal Pengabdian Bidang Kesehatan, 2024)
School-age children are a group vulnerable to nutritional problems. Their nutritional status is crucial as it affects cognitive abilities and health. Therefore, measuring nutritional status becomes a necessary preventive step. This activity was carried out on September 18, 2024, with the aim of measuring and assessing the nutritional status of elementary school children using anthropometric methods to measure weight and height, and evaluating nutritional status based on BMI-for-age. The event was successful, with active participation from the students of SDN Centre Number 1 Pattallassang, Kab. Takalar, and received appreciation from the school. The results showed that 2 children were obese, 1 child was undernourished, and 32 children had a good nutritional status. Regular assessments and intervention from relevant agencies are highly needed.